THE CONSTITUTION – THE SUPREME SOURCE OF ROMANIAN LAW? - STROE, Georgiana – Magdalena (International Journal of Legal and Social Order, 2022)
The purpose of this article is to conduct an analysis of the dynamics between the principle of constitutional supremacy and the principle of priority application of European Union law. Starting from a question and still asking questions, this article is intended to be a preamble for debates:, what is the difference between priority and supremacy?”, “does the European Union have good reasons to be concerned about certain decisions pronounced at national level?”, “is there a need for a reinterpretation of the normative hierarchy?”… For some of these questions I will try to answer, but for the rest, at this moment, the answer would / could be uncertain or non-existent.